2021
DOI: 10.3390/en14216925
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to and Drivers of Energy Management in Swedish SMEs

Abstract: The energy efficiency gap is known as the difference between optimal level of energy efficiency and the actual level of achieved energy efficiency. Energy management has proven to further close the energy efficiency gap. Energy management may differ depending on whether it concerns a large, energy-intensive company or small and medium-sized enterprises (SMEs). SMEs are of high interest since they form a large share of the economy today. For SMEs, a lighter form of energy management, in the form of energy effic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 67 publications
(156 reference statements)
0
12
0
Order By: Relevance
“…Thus, one key conclusion is that standards, energy KPIs, and general approaches to and methods of supply chain EnM need to be explored and developed. Considering that most of the large companies' suppliers are SMEs (Szczepański, 2021), there is a great opportunity to reduce scope 3 GHG emissions by developing standards that support these upstream suppliers in overcoming the barriers to implementing EEMs, for instance, lack of time, resources and knowledge as identified in previous studies (Jalo et al, 2021a). This will not only reduce the upstream scope 3 emissions from large companies but also increase the profitability of both suppliers and focal companies.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, one key conclusion is that standards, energy KPIs, and general approaches to and methods of supply chain EnM need to be explored and developed. Considering that most of the large companies' suppliers are SMEs (Szczepański, 2021), there is a great opportunity to reduce scope 3 GHG emissions by developing standards that support these upstream suppliers in overcoming the barriers to implementing EEMs, for instance, lack of time, resources and knowledge as identified in previous studies (Jalo et al, 2021a). This will not only reduce the upstream scope 3 emissions from large companies but also increase the profitability of both suppliers and focal companies.…”
Section: Discussion and Recommendationsmentioning
confidence: 99%
“…In the last decades, several articles studied the implementation of in-house energy efficiency measures in large industrial companies (Lawrence et al, 2019;Andersson, 2020). However, small and medium-sized enterprises (SMEs), which are a significant proportion of suppliers to large industrial companies, usually do not have the resources to implement EnM in their companies (Jalo et al, 2021a). Frequently, SMEs have a lack of economic resources, time, knowledge, and awareness to implement energy efficiency (Marchi and Zanoni, 2017;Jalo et al, 2021a).…”
Section: Energy Efficiency In Industrymentioning
confidence: 99%
“…the difference between optimal level of energy efficiency and the actual level of achieved energy efficiency). Relatively few energy management drivers have been identified, as opposed to the more numerous identified drivers of energy efficiency or specific energy efficiency measures (Jalo et al, 2021). Some of the most significant barriers to energy efficiency in SMEs identified in Jalo et al (2021) are as follos: a lack of time/other priorities, prioritisation of non-energy related working tasks and an organisational structure that does not facilitate consideration of sustainability and energy efficiency.…”
Section: Previous Researchmentioning
confidence: 99%
“…Relatively few energy management drivers have been identified, as opposed to the more numerous identified drivers of energy efficiency or specific energy efficiency measures (Jalo et al, 2021). Some of the most significant barriers to energy efficiency in SMEs identified in Jalo et al (2021) are as follos: a lack of time/other priorities, prioritisation of non-energy related working tasks and an organisational structure that does not facilitate consideration of sustainability and energy efficiency. The limitation of the study is that only data from Swedish SMEs was considered, and the numerous barriers found were grouped into organisational, knowledge-related and economic barriers, which limits identification of the institutional 'regulatory' issues and more subtle differences which may exist between the organisational and individual levels.…”
Section: Previous Researchmentioning
confidence: 99%
“…Energy management systems are not yet widespread among EU SMEs [128]. Some reviews cover the implementation of EnMS in SMEs at the global level [16,34,129], highlighting that energy management standards (mainly ISO 50001) are often too complex for a costeffective implementation at the SME level (for non-energy-intensive companies [130]) and alternative tools for energy management should be tailored to SMEs (i.e., networks [109], inhouse tools [131], plan-do-check-act cycle tools [132], integrated decision support systems tools [133], or external support [134]). Hence, their implementation in SMEs in simplified forms should be taken into consideration by policymakers.…”
mentioning
confidence: 99%